(3EOGQI GdafGObs - (3CMeO eMeO(B, (3GdeUQjs ((3GdGScfOQjI(B:s (3eDSSI THGH GdLGeYI(B,s, 1998)
(3GdbhGYO GdYGeI ddGOGQI, GOGQI GdafGOb, CfhGY GdafGOb, GdJfXje GdOGNdj ddafOb, GdYeGdI aj GdafGOb, Cge GdeTGcd GdJj JhGLg GOGQI GdafGObs
(3GdeQGLY U(B.97s
Keywords: (3GdSjGMIs; (3GdafGOb, GdGOGQIs